Oxford Video Informed Consent Tool (OxVIC): a pilot study of informed video consent in spinal surgery and preoperative patient satisfaction - Victoria Williamson; Gerard Mawhinney; Chrishan Thakar; Dominique A Rothenfluh; Jeremy Reynolds (BMJ Open)
Objectives The British Association of Spinal Surgeons recently called for updates in consenting practice. This study investigates the utility and acceptability of a personalised video consent tool to enhance patient satisfaction in the preoperative consent giving process.Design A single-centre, prospective pilot study using questionnaires to assess acceptability of video consent and its impacts on preoperative patient satisfaction.Setting A single National Health Service centre with individuals undergoing surgery at a regional spinal centre in the UK.Outcome measure As part of preoperative planning, study participants completed a self-administered questionnaire (CSQ-8), which measured their satisfaction with the use of a video consent tool as an adjunct to traditional consenting methods.Participants 20 participants with a mean age of 56 years (SD=16.26) undergoing spinal surgery.Results Mean patient satisfaction (CSQ-8) score was 30.2/32. Median number of video views were 2–3 times. Eighty-five per cent of patients watched the video with family and friends. Eighty per cent of participants reported that the video consent tool helped to their address preoperative concerns. All participants stated they would use the video consent service again. All would recommend the service to others requiring surgery. Implementing the video consent tool did not endure any significant time or costs.Conclusions Introduction of a video consent tool was found to be a positive adjunct to traditional consenting methods. Patient–clinician consent dialogue can now be documented. A randomised controlled study to further evaluate the effects of video consent on patients’ retention of information, preoperative and postoperative anxiety, patient reported outcome measures as well as length of stay may be beneficial.